KISARAN INANG DAN DINAMIKA POPULASI Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) DI PERTANAMAN CABAI MERAH - . Hendrival; Purnama Hidayat; Ali Nurmansyah (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
The study of host range and population dynamic of B. tabaci in red chili pepper fiel dswas conducted in Sub-district of Pakem, District of Sleman, Province of Daerah Istimewa Yogyakarta during dry season of May-October 2009. The study of host plants of B. tabaci from the red chili pepper fields revealed that there were 27 species of host plants belong to 22 genera of 13 families including crops and weeds. The host plants belong to families of Araceae, Amaranthaceae, Asteraceae, Brassicaceae, Capparidaceae, Convolvulaceae, Euphorbiaceae, Lamiaceae, Oxalidaceae, Papilionaceae, Rubiaceae, Solanaceae and Sterculiaceae. The host plant families of Asteraceae and Euphorbiaceae had the most abundant population of B. tabaci. Geminivirus-like symptoms were found in the weeds of A. conyzoides and A. boehmerioides. Population of B. tabaci adults correlated with abundance of host plant species found in the red chili pepper fields. The population of B. tabaci in red chili pepper fields was affected by natural enemy population. Population dynamic of the parasitoid Eretmocerus sp. correlated with population dynamic of the parasitized nymph of B. tabaci. Parasitoid Eretmocerus sp. was potentially good in controlling population of B. tabaci nymph in red chili pepper fields.